الاتجاه اللغوي لمعنى الاستواء وأثر الاعتزال فيه عند الزمخشري من خلال تفسيره الكشاف - Yahaya, Nasir; Samaila, Ali; Adam, Faiz Shuaib; Lul Abdul Ghani, Mubarak (Jurnal Studi Al-Qur'an, 2024)
Islamic thought has produced many intellectual and scientific schools, within which many personalities in different scientific fields have emerged. Al-Zamakhshari (d. 538H) is regarded as one of the most influential figures from the Mu’tazila school of thought in the history of Arab and Islamic culture. This study aims to reveal the direction and impact of Mu'tazila thought on the interpretation of verses related to Istiwa through Zamakhshari's book "Al-Kashaf" to expand the definition of the linguistic meanings presented by Al-Zamakhshari and analyze the contexts in which he dealt with this concept. The significance of this article lies in understanding the mechanisms of interpretation upon which Al-Zamakhshari relied in defending his belief by using reasoning and language to disassociate and free the Almighty from being similar or resembling the creature. The research used the descriptive-analytical approach to highlight the aspects used in al-Zamakhshari's interpretation of the concept of Istiwa. The study finds that the interpretations of the verses related to al-Istiwa Zamakhshari are purely linguistic-based interpretations, which he employs and links to the significance and context meaning according to what supports his Mu’tazili doctrine.